PERANCANGAN DESAIN CLAY STARTER KIT BAGI PEMULA - Adella Artamevia Putri; Wyna Herdiana; Brian Kurniawan Jaya (Perpustakaan Universitas Surabaya, 2022)
Abstract‐Clay crafts are hand skills using clay materials that are ductile, easy to shape, and soft. Dough clay has evolved from clay to other alternatives such as flour clay. Flour clay is made from various types of flour, namely cornstarch, tapioca flour, and rice flour in a ratio of 1:1:1 mixed with white glue and a little oil. Currently, clay crafts have developed into jewelry, miniatures, souvenirs, and others. Seeing the variety of clay crafts, individuals began to see these crafts in business opportunities. In career search, individuals at the age of 18‐24 years are in the exploratory phase, where individuals begin to find out their intended career interests. The product design, namely Krafen, is useful for beginners in learning clay crafts anywhere. The product is designed to be easy to carry and use without worrying about getting messy with an easy‐to‐understand manual book. The product consists of packaging made of cardboard with geometric shapes with a visual display of Memphis designs and the use of colliding colors, namely primary colors. The product is equipped with basic equipment for kneading and shaping the dough using an acrylic work mat, acrylic grinder, sculpting tools, and silicone. Followed by the coloring process using brushes, acrylic paints, and soft pastels. The final stage (finishing) is varnishing and adding accessories to the work. Abstrak‐Kerajinan tangan clay merupakan keterampilan tangan menggunakan material clay yang bersifat ulet, mudah dibentuk, dan lunak. Adonan clay telah berkembang dari tanah liat menjadi alternatif lain seperti clay tepung. Clay tepung terbuat dari beragam jenis tepung, yaitu tepung maizena, tepung tapioka, dan tepung beras dengan perbandingan 1:1:1 yang dicampur lem putih dan sedikit minyak. Kerajinan tangan clay saat ini telah berkembang menjadi perhiasan, miniatur, souvenir, dan lain‐lain. Dengan berkembangnya kerajinan clay, individu mulai melihat perkembangan tersebut dalam peluang bisnis. Dalam pencarian karir, individu pada usia 18‐24 tahun merupakan fase realistic, dimana individu mulai mencari tau minat karir yang dituju. Peracangan desain produk, yaitu Krafen berguna untuk pemula dalam belajar kerajinan tangan clay dimana saja. Produk dirancang untuk mudah dibawa dan digunakan tanpa rasa khawatir akan berantakan dengan buku panduan yang mudah dipahami. Produk terdiri dari kemasan yang terbuat dari kardus berbentuk geometri dengan tampilan visual desain Memphis dan penggunaan warna bertabrakan yaitu warna primer. Produk dilengkapi dengan peralatan dari dasar menguleni dan membentuk adonan menggunakan alas kerja akrilik, penggiling akrilik, alat membentuk (sculp tools), dan silikon. Dilanjutkan dengan proses pewarnaan menggunakan kuas, cat acrylic, dan softpastel. Tahap akhir (finishing) dilakukan pengusapan cairan varnsish dan tambahan aksesoris pada karya.